The impact of resilience on L2 learners' motivated behaviour and proficiency in L2 learning. Issue 1 (1st January 2017) - Kim, Tae-Young; Kim, Yoon-Kyoung
Abstract: This exploratory study focused on the factors that constitute second language (L2) learners' resilience, and how these factors are related to L2 learning by investigating what relation resilience may have to motivated behaviour and proficiency in English learning. A total of 1620 secondary school learners of English participated in a questionnaire survey. By analysing the quantitative data, five resilience factors were extracted: perceived happiness, empathy, sociability, persistence, and self-regulation. Confirmative factor analysis using AMOS proved that these five factors are distinctive constructs. Among the factors, persistence was identified to play the most influential role in L2 learning. Persistence showed the highest correlations with, and the strongest explanatory power for, motivated behaviour and English proficiency. It is suggested that resilience can be further explored as an individual differences factor in L2 learning, which is involved in L2 learning process and outcomes.